Corporate Actions and Islamic Bank Performance: A Generalized Synthetic Control Evidence from Bank Muamalat Indonesia - Fadlha, Sulthan Arief; Fathurrohman, Muhamad Said (Universitas Airlangga, 2025)
This study aims to evaluate the impact of corporate actions implemented by Bank Muamalat Indonesia (BMI) in 2018 on aspects of profitability, capital adequacy, and financing quality, compared to other Islamic banks. The method used is Generalized Synthetic Control (GSC), which allows comparison between BMI that performs corporate actions and Islamic banks that do not. The data analyzed includes Net-Operating Margin (NOM), Return On Asset (ROA), and Net Income (NI) ratios to measure profitability, Capital Adequacy Ratio (CAR) for capital adequacy, and Non-Performing Financing (NPF) for financing quality, with a sample of 8 Islamic banks. The results show that there is a significant positive effect of corporate action of asset sales on NPF in a certain period, while CAR is not significantly affected by corporate action rights issues. For profitability ratios, only the NI ratio showed a significant negative effect, while ROA and NOM were not significantly affected, although both experienced a decline after the corporate action. These findings suggest that the impact of corporate actions varies depending on the conditions of each bank, and can be used by management to plan appropriate corporate action policies in corporate strategy.